SOCIO-HISTORICAL FOUNDATIONS OF GENEALOGICAL NARRATIVES - Jo‘rayeva Azizabonu Ulug‘bek qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article explores genealogical narratives as a key framework for understanding origin, continuity, and identity. It traces their development from oral kinship traditions to complex literary forms across Eastern and Western cultures. The study argues that genealogy functions not only as a record of descent but also as a narrative structure shaping cultural memory and literary expression. Ultimately, it highlights genealogy as a lasting narrative logic in literature.